Achieving Sustainability of the Energy Sector in Canada - Mourougane, Annabelle (OECD Economics Department Working Papers, 2008)
Energy represents a major sustainable-development challenge for Canada. In the short term, labour shortages and infrastructure bottlenecks are likely to hinder energy developments and need to be addressed. In addition, provincial fiscal management could be improved by adopting prudent allocation and withdrawal rules of revenues from non-renewable resources to and from a long-term fund. Eventually the main challenge will be to curb greenhouse gas emissions (GHGs), despite the rapid expansion of high emitting sectors. The effectiveness of environmental policies could be enhanced by better federal-provincial coordination. Efforts should be concentrated on designing and implementing an emissions-trading scheme compatible with corresponding systems abroad. Finally, effective and efficient systems of regulation and taxation are essential to facilitate the timely realisation of energy supply plans